Enforcement Of The Practice Of Illegal Fees (Illegal Fees) In The Vehicle Inspection: Penegakan Hukum Praktek Pungutan Liar (Pungli) Dalam Uji KIR - Pradhista, Vendira De; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2021)
The KIR test is a mandatory requirement for certain public vehicles to test the feasibility of operating on the road, the KIR test mechanism implemented at the Transportation Service in several regions in Indonesia still has a series of problems. One of them is illegal levies at the stage of tapping the KIR test number for new cars. This problem is indicated to have occurred at the Transportation Agency of Sidoarjo Regency, where illegal levies occurred with the updated KIR test mechanism. This writing discusses how to enforce the law on extortion, why it can happen in the updated KIR test mechanism, then whether law enforcement carried out by the perpetrators is in accordance with legal provisions. This writing uses a sociolegal research method with a sociological juridical approach, through inductive analysis, aiming to answer legal issues in this paper. The results of the study explain that law enforcement on illegal levies has not been implemented according to legal provisions due to several factors, also because illegal levies are not known by internal parties due to the lack of supervision during implementation.